Synergistic effect of 1-(2, 5-dioxoimidazolidin-4-yl)urea and Tween-80 towards the corrosion mitigation of mild steel in HCl. (16th August 2019) - Zhang, Weiwei; Li, Hui-Jing; Wang, Chen; Wang, Li-Juan; Li, Gen; Ma, Hengyu; Pan, Qianwen; Wu, Yan-Chao
Abstract : The inhibition performance and synergistic inhibition effect of DMU with Tween-80 on the corrosion of mild steel in 1 M HCl was studied for the first time. Abstract : Herein, the synergistic effect of 1-(2, 5-dioxoimidazolidin-4-yl)urea (DMU) and Tween-80 on the corrosion of mild steel in a 1 mol L −1 HCl solution was investigated by weight-loss tests, electrochemical methods and surface analysis (SEM/SECM). The experiments revealed that the combination of DMU and Tween-80 strongly inhibited the corrosion of mild steel as compared to individual inhibitors, and the adsorption mode belonged to the Langmuir isothermal type. Based on the electrochemical results, DMU and DMU–Tween-80 behaved as mixed-type inhibitors, and their best inhibition efficiencies were 77.31% and 96.35%, respectively. The calculated synergistic parameter value was larger than unity, indicating that the enhancement of inhibition efficiency was due to the synergistic effect of DMU and Tween-80. Surface analysis techniques confirmed the presence of inhibitors on the mild steel surface. Quantum chemical parameters based on density functional theory provided a further insight into the mechanism of inhibition. Moreover, molecular dynamics simulations were carried out to explore the configurational adsorption behaviour of DMU on an Fe(110) surface.